علاقة الإعلام الجديد بتعزيز الثقافة البيئية في الوسط المدرسي وتحقيق التنمية للمجتمع المحلي. قراءة سوسيوإتصالية - ذيب, محمد; بلعيد, محمد (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الورقة البحثية للكشف عن دور الإعلام الإيجابي في تعزيز الثقافة البيئية وتحقيق التنمية في المجتمع من خلال الترابط والتمازج مع الوسط المدرسي والتربوي لتحقيق ذلك، من خلال الحملات الإعلامية الهادفة للحفاظ على البيئة وتنمية المجتمع، ومن خلال الحفاظ على البنية التحتية الإقتصادية والإجتماعية وكذا الثقافية وتوعية المجتمع بالحفاظ على كل ماهو أساسي لتحقيق التنمية وترقية المجتمع والبلد إلى الأفضل، من خلال نشر الوعي الفكري ونضجه لدى أفراد المجتمع، كما أن المدرسة لها دور كبير في تحقيق التوعية والثقافة البيئية بإعتبارها من مؤسسات التنشئة الإجتماعية التي تساعد في النهوض بالقطاع البيئي ومن أجل تحقيق التطور والتقدم، وعليه هذه الورقة دراسة وصفية تحليلية للوضع الراهن للإعلام ودوره في نشر الوعي والأفكار الخلاقة مناصفة مع المدرسة التي تعتبر المحور الأساسي في كيان المجتمع، لتمرير هذه الأفكار لأجل الحفاظ على البيئة وترقية الخدمات الإجتماعية لتحقيق الثقافة البيئية والحفاظ على البيئة، ولعل من أهم النتائج التي سنتوصل إليها هي تفعيل دور الإعلام في تحقيق التنمية وتعزيز الثقافة البيئية من خلال إشراك الفرد والمجتمع المدني في الحفاظ على البيئة وتحقيق التنمية ورفع المستوى الثقافي في المدرسة. This research paper aims to uncover the role of positive media in promoting environmental culture and achieving development in society through interconnectedness and mixing with the school and educational milieu to achieve this through media campaigns aimed at preserving the environment and developing society by preserving the economic and social infrastructure as well as cultural and community awareness By preserving everything essential to achieving development and promoting the society and the country to the better by spreading intellectual awareness and maturity among members of society, and the school has a major role in achieving awareness and environmental culture as one of the social upbringing institutions that help to advance the environmental sector and in order to achieve development and progress. Accordingly, this paper is a descriptive and analytical study of the current situation of the media and its role in spreading awareness and creative ideas equally with the school which is the main focus of passing these ideas in order to preserve the environment and promote social services in order to achieve environmental culture and preserve the environment, and perhaps one of the most important results that we will reach is to activate the role of the media in achieving development and enhancing environmental culture by involving the individual and civil society in preserving On the environment.
The relationship of the new media to promoting environmental culture in the school environment and achieving development for the local community- Sociocommunicative reading-
مقال
Keywords: إعلام، بيئة، تنمية، مدرسة، مجتمع.; Community; Environment, School, Development, Media.